Urgensi Kontekstualisasi dan Rekonstruksi Kurikulum Pendidikan Agama Islam di Sekolah - Suparta Suparta (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
The Islamic Religious Education Curriculum is compiled, of course, has a very noble purpose, especially for students. However, if the Islamic Religious Education curriculum is not structured carefully, what happens is not educating students to be good-spirited and of good character, but on the contrary they can behave radically and exclusively. So that Islamic religious education should have a transformative face, i.e. presuppose a dialectic between normative-doctrinal and socio-cultural aspects, text and context, ideals and reality, in fact it becomes radical and exclusive. Thus there must be the development of an Islamic religious education curriculum that can be contextualized with the historical-sociological reality of the lives of students. Contextualization here is very necessary so that students cannot be separated from their socio-cultural roots. In addition, so that Islamic religious education does not only produce students' personalities who are intellectually intelligent but spiritually poor. Or if you take the term Prof. Hamka is a human figure who is intelligent but does not have a superior personality, namely intellectual superiority and spiritual excellence in the language of the Koran called Ulil Albab. Keywords: Abstract Kurikulum Pendidikan Agama Islam disusun tentunya memiliki tujuan yang sangat mulia terutama bagi peserta didik. Namun demikian, jika kurikulum Pendidikan Agama Islam tersusun tidak dengan hati – hati maka yang terjadi bukan mendidik peserta didik menjadi berjiwa dan berkarakter yang baik tapi sebaliknya bias menjadi berprilaku radikal dan eksklusif. Sehingga yang seharusnya pendidikan agama Islam berwajah transformative yakni mengandaikan adanya dialektika antara aspek normatif-doktrinal dan sosiologis-kultural, teks dan konteks, idealitas dan realitas justru menjadi berwajah radikal dan ekslusif. Dengan demikian harus ada pengembangan kurikulum pendidikan agama Islam yang dapat dikontekstualisasikan dengan realitas historis-sosiologis kehidupan peserta didik. Kontekstualisasi di sini sangat diperlukan supaya peserta didik tidak terlepas dari akar sosial-kulturalnya. Selain itu agar pendidikan agama Islam tidak hanya menghasilkan kepribadian siswa yang cerdas secara intelektual tapi miskin spiritual. Atau jika mengambil istilah prof Hamka adalah sosok manusia yang pandai tetapi tidak memiliki pribadi yang unggul yaitu unggul intelektual dan unggul spiritual dalam Bahasa Al-Quran di sebut Ulil Albab. Kata Kunci:Kurikulum Pendidikan Agama Islam, Urgensi Kurikulum, Rekonstrui Kurikulum